Numerical study of the compressive mechanical behaviour of rubberized concrete using the eXtended Finite Element Method (XFEM). (1st November 2017) - Duarte, A.P.C.; Silvestre, N.; de Brito, J.; Júlio, E.
Abstract: In this paper, a plane stress finite element model was developed to study the behaviour of a rubberized concrete (RuC) cubic specimen subjected to uniaxial compressive loading. To obtain the geometry of the given RuC section, specifically the heterogeneous distribution of rubber aggregates within the concrete matrix, MATLAB Image Processing is used. Then, to allow the initiation, opening and propagation of cracks in the concrete matrix upon loading, which ultimately lead to the failure of the RuC cube cross-section, a numerical model based on the eXtended Finite Element Method (XFEM) is implemented. The study motivation and the research significance are first presented. Then, the experimental programme conducted to characterize RuC's main mechanical properties is described. Both the image-processing and the numerical analysis of the proposed mechanical model are described, with emphasis on the implementation and calibration of XFEM to allow for multiple cracks to develop in the RuC section. The numerical results are validated based on the experimental data and a detailed study on the post-cracked behaviour of the RuC section is presented and lastly, some conclusions are drawn.